2017
DOI: 10.24896/jmbr.2017714
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Evaluation of Computational and Experimental Analysis of Polyphenol Oxidase from Cocoa (Theobroma cacao L.)

Abstract: Cocoa (Theobroma cacao L.) is a cash crop of huge economic significance in the world

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…The WoLFPSORT prediction showed that βamylase of sweet potato (Ipomoea batata) is an extracellular enzyme as also confirmed in by other scientific researches [6,8,27]. Amino acid sequence VNADN was predicted as the signal Although, it has not been reported that β-amylase undergoes any glycosylation for its activities.…”
Section: Resultsmentioning
confidence: 62%
“…The WoLFPSORT prediction showed that βamylase of sweet potato (Ipomoea batata) is an extracellular enzyme as also confirmed in by other scientific researches [6,8,27]. Amino acid sequence VNADN was predicted as the signal Although, it has not been reported that β-amylase undergoes any glycosylation for its activities.…”
Section: Resultsmentioning
confidence: 62%